Effects of agronomic treatments on structure and function of ammonia-oxidizing communities - Phillips, Carol J., author; Paul, Eldor A., author; Prosser, James I., author; Gross, Katherine L., author; Dollhopf, Sherry L., author; Harris, Dave, author; American Society for Microbiology, publisher (Colorado State University. Libraries, 2000)
The aim of this study was to determine the effects of different agricultural treatments and plant communities on the diversity of ammonia oxidizer populations in soil. Denaturing gradient gel electrophoresis (DGGE), coupled with specific oligonucleotide probing, was used to analyze 16S rRNA genes of ammonia oxidizers belonging to the β subgroup of the division Proteobacteria by use of DNA extracted from cultivated, successional, and native deciduous forest soils. Community profiles of the different soil types were compared with nitrification rates and most-probable-number (MPN) counts. Despite significant variation in measured nitrification rates among communities, there were no differences in the DGGE banding profiles of DNAs extracted from these soils. DGGE profiles of DNA extracted from samples of MPN incubations, cultivated at a range of ammonia concentrations, showed the presence of bands not amplified from directly extracted DNA. Nitrosomonas-like bands were seen in the MPN DNA but were not detected in the DNA extracted directly from soils. These bands were detected in some samples taken from MPN incubations carried out with medium containing 1,000 μg of NH4+-N ml−1, to the exclusion of bands detected in the native DNA. Cell concentrations of ammonia oxidizers determined by MPN counts were between 10- and 100-fold lower than those determined by competitive PCR (cPCR). Although no differences were seen in ammonia oxidizer MPN counts from the different soil treatments, cPCR revealed higher numbers in fertilized soils. The use of a combination of traditional and molecular methods to investigate the activities and compositions of ammonia oxidizers in soil demonstrates differences in fine-scale compositions among treatments that may be associated with changes in population size and function.
Publisher version: https://aem.asm.org/content/66/12/5410.full.
Keywords: soils; ammonia oxidizer populations; nitrification; microbial communities; ammonia oxidation; soil cultivation